Chip-based quantum key distribution - P. Sibson (Nature Portfolio, 2017)
Quantum key distribution has not been widely adopted in part due to technical hurdles preventing it being fully integrated in classical communication networks. Here the authors report quantum key distribution between two photonic chips manufactured with state-of-the-art telecoms industry processes.